Studying the Impact of Administrative Empowerment As a Mediating Variable in the Relationship between Organizational Commitment and Administrative Creativity: A Field Study in the Jordanian Pharmaceutical Companies in Light of Covid - 19 - Al-Khawaldah, Reyad A. (Jordan Journal of Business Administration, 2023)
Managerial creativity enhances the distinction of any organization compared to other organizations due to its ability to find suitable solutions for the problems facing the organization and due to its ability to improve new products and services or through improving working methods or styles in it. Therefore, this topic has occupied a large area of interest in literature review. However, there are some aspects which are still ambiguous about the impact of each of the organizational commitment and administrative empowerment on one hand and administrative creativity on the other hand, especially in light of the COVID-19 pandemic which the world is suffering from nowadays. Accordingly, this study aims to investigate the impact of organizational commitment, with its various dimensions, on administrative creativity within the Jordanian pharmaceutical companies with the existence of administrative empowerment as a mediating variable. Data of the study was collected using a simple random sample which consisted of (201) employees working in the Jordanian pharmaceutical companies. Structural equation modeling (SEM) analysis was conducted using AMOS.20. The study found that there are strong correlation relationships between most of the study variables in addition to the existence of a significant impact of administrative empowerment on administrative creativity as a dependent variable. The (direct and indirect) results of the total impact analysis revealed that there is an impact of all dimensions of organizational commitment on administrative creativity with the existence of administrative empowerment as a mediating variable. Based on these results, the study recommended that Jordanian pharmaceutical companies conduct workshops, seminars and training programs to teach their employees the importance of organizational commitment and occupational empowerment and their role in enhancing administrative creativity. In addition, the investigated companies need to pay attention to involving their employees in setting goals, formulating policies and programs, participating in decision-making processes and spreading a culture of teamwork by providing incentives of various kinds, which contributes to enhancing the levels of organizational commitment and administrative creativity alike, especially in light of Covid-19 pandemic.